THE INFLUENCE OF ARTIFICIAL INTELLIGENCE LITERACY ON LEADERSHIP EFFECTIVENESS IN FINANCE INDUSTRY - Yonghwa Han; Andini Nurwulandari; Hasanudin (PT. Jurnal Center Indonesia Publisher, 2025)
This research investigates the impact of AI literacy on leadership effectiveness within the finance industry, a sector experiencing rapid digital transformation. As artificial intelligence becomes increasingly integrated into financial operations, leaders are required to possess not only traditional managerial skills but also a strong understanding of AI concepts, applications, and ethical considerations. Using a quantitative approach, data were collected from 55 finance professionals occupying leadership roles across various organizations. The study assessed their levels of AI literacy and examined its relationship with their perceived leadership effectiveness. The results reveal a significant positive correlation between AI literacy and leadership effectiveness, indicating that leaders with higher AI literacy are better equipped to drive innovation, make strategic decisions, and successfully adapt to technological change. These findings highlight the importance of integrating AI literacy into leadership development programs and fostering a culture of continuous learning to ensure sustained organizational agility and competitiveness in the finance sector.